Pengaruh Stabilitas Politik, Indeks Demokrasi, dan Foreign Direct Investment terhadap Pertumbuhan Ekonomi Negara Anggota OKI di Kawasan MENA Tahun 2020-2024 - Lailia, Khusnul; Muthohar , Ahmad Mifdlol (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to analyze the effect of political stability, democracy index, and Foreign Direct Investment (FDI) on economic growth in member countries of the Organization of Islamic Cooperation (OIC) in the Middle East and North Africa (MENA) region for the period 2020–2024. This study uses a quantitative approach with a panel data analysis method that combines cross-section and time series data. The data used is secondary data obtained from the World Bank, the International Monetary Fund (IMF), the Economist Intelligence Unit, and Worldwide Governance Indicators. The analysis models used include the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM), with the selection of the best model through Chow, Hausman, and Lagrange Multiplier tests. The results of the study show that political stability does not have a significant effect on economic growth, while the democracy index and Foreign Direct Investment (FDI) have a positive and significant effect on economic growth. Simultaneously, political stability, the democracy index, and FDI have a significant effect on economic growth.